1997
DOI: 10.1038/sj.cdd.4400314
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cell death and cytokine dysregulation in human immunodeficiency virus infection: pivotal factors in disease progression

Abstract: The progressive loss of CD4 T lymphocyte is patognomonic of Human Immunodeficiency Virus (HIV) infection and results in immunodeficiency and the appearance of acquired immunodeficiency syndrome (AIDS)-defining pathologies. Although a percentage of CD4 T lymphocytes is destroyed directly by HIV infection, a much higher proportion of lymphocytes remains uninfected and therefore must be destroyed by mechanisms not directly involving viral infection. One such mechanism is apoptotic T cell death (ATCD). ATCD in HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…However, assaying CD4+ T cell numbers alone is inadequate for HIV monitoring, since the normal T lymphocyte reference range of the study population has enormous variation due to age, sex, and other factors (Amatya et al, 2004;McCune, 2001). The PVL provide an accurate measure to identify new infections, monitor disease progression and response to ART (Clerici et al, 1997;Ho et al, 1995;Katzenstein and Holodniy, 1995;Wei et al, 1995). Chronic immune activation detected by the co-expression of CD38 and HLA-DR on CD4+ and CD8+ T-cells correlates with disease progression (Clerici et al, 1997;Swanson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, assaying CD4+ T cell numbers alone is inadequate for HIV monitoring, since the normal T lymphocyte reference range of the study population has enormous variation due to age, sex, and other factors (Amatya et al, 2004;McCune, 2001). The PVL provide an accurate measure to identify new infections, monitor disease progression and response to ART (Clerici et al, 1997;Ho et al, 1995;Katzenstein and Holodniy, 1995;Wei et al, 1995). Chronic immune activation detected by the co-expression of CD38 and HLA-DR on CD4+ and CD8+ T-cells correlates with disease progression (Clerici et al, 1997;Swanson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The PVL provide an accurate measure to identify new infections, monitor disease progression and response to ART (Clerici et al, 1997;Ho et al, 1995;Katzenstein and Holodniy, 1995;Wei et al, 1995). Chronic immune activation detected by the co-expression of CD38 and HLA-DR on CD4+ and CD8+ T-cells correlates with disease progression (Clerici et al, 1997;Swanson et al, 2005). These parameters have not been well defined in HIV-1 C infection.…”
Section: Introductionmentioning
confidence: 99%
“…Comorbid clinical depression and some symptoms of AIDS are similar, such as poor appetite, weight loss, and cognitive impairment. It has been shown that inflammatory cytokines can contribute to these symptoms (Dantzer and Kelley 1989;Clerici et al 1997). …”
Section: Stress and Hivmentioning
confidence: 99%
“…While apoptosis plays essential roles in immune regulation, it can be pathogenic where it interferes with the generation and renewal of effector cells, as appears to be the case in HIV infection. 10,11 The causes of lymphocyte apoptosis in HIVinfected individuals are multi-factorial and are believed to include TCR/CD3 triggering in the absence of appropriate co-stimulation, CD95-CD95 ligand interactions and gp120-CD4 interactions. 10,11 In addition, alterations in the profile of cytokine production and deprivation of growth factors arising from deletion of lymphocyte populations can contribute to further lymphocyte loss.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The causes of lymphocyte apoptosis in HIVinfected individuals are multi-factorial and are believed to include TCR/CD3 triggering in the absence of appropriate co-stimulation, CD95-CD95 ligand interactions and gp120-CD4 interactions. 10,11 In addition, alterations in the profile of cytokine production and deprivation of growth factors arising from deletion of lymphocyte populations can contribute to further lymphocyte loss. 11,12 Freshly isolated lymphocytes of HIV-infected individuals are highly susceptible to apoptosis following short-term culture in the absence of exogenous cytokines, commonly referred to as spontaneous apoptosis, and to apoptosis induced in vitro by mitogens, recall antigens and monoclonal antibodies (mAbs) directed against the CD3 and CD95 molecules.…”
Section: Introductionmentioning
confidence: 99%